The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/su11226290
|View full text |Cite
|
Sign up to set email alerts
|

A New Attitudinal Integral-Model to Explain Green Purchase Intention

Abstract: : This study explores the relationship between different implicit and explicit attitudes and green purchase intention. A distinction is made between the cognitive and affective components of implicit attitudes. Negative-oriented attitudes such as cynicism and skepticism are also examined. The data collection process provided 724 responses to two online Implicit Association Tests, followed by a questionnaire on explicit attitudes. Two products (insecticide and toothpaste) in green and conventional formats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…People with greater knowledge of environmental problems and methods of eradicating them showed a stronger inclination towards purchasing green products [41][42][43][44]. There were also attempts to incorporate other factors such as habits, past experiences of the product [48], cynicism and skepticism [49]. Many studies [18,39,50] have indicated that sociodemographic factors, i.e., gender, age, educational background, personal circumstances and children in the household, affect green purchase behavior.…”
Section: Green Purchase Behaviormentioning
confidence: 99%
“…People with greater knowledge of environmental problems and methods of eradicating them showed a stronger inclination towards purchasing green products [41][42][43][44]. There were also attempts to incorporate other factors such as habits, past experiences of the product [48], cynicism and skepticism [49]. Many studies [18,39,50] have indicated that sociodemographic factors, i.e., gender, age, educational background, personal circumstances and children in the household, affect green purchase behavior.…”
Section: Green Purchase Behaviormentioning
confidence: 99%
“…Third, consumers are opting for greener options, and this opportunity can ameliorate policymakers' green strategies and functions (Sharma and Paço, 2021). Fourth, consumers are cynical regarding green products (Sarabia-Andreu et al, 2019), and apprehension regarding greenwashing is intensifying . These critical issues can be resolved when firms are engaged in environmental modernization and consumers are aware of these innovations.…”
Section: Introductionmentioning
confidence: 99%
“…As such, understanding the key factors that contribute to the formation of consumer purchase intention (PI) towards environmentally friendly apparel is crucial when developing effective marketing strategies. To explore this, consumer PI, a worthy and well-studied extension of Planned Behavior Theory [26], is commonly accepted as an important index to predict PI [27], a consumer's declaration of a predisposition to purchase, barring any significant contingencies in the market or the consumer's personal situation [28].…”
Section: Introductionmentioning
confidence: 99%